Polyclonal but not monoclonal circulating memory CD4+ T cells attenuate the severity of Staphylococcus aureus bacteremia - Braverman, Jessica; Monk, Ian R.; Zhang, Heran; Stinear, Timothy P.; Wakim, Linda M. (Frontiers in Immunology, 2024)
Staphylococcus aureus bacteraemia causes significant morbidity and mortality. Treatment of staphylococcal infections is hindered by widespread antibiotic resistance and attempts to develop an S. aureus vaccine have failed. Improved S. aureus treatment and infection prevention options require a deeper understanding of the corelates of protective immunity. CD4 + T cells have been identified as key orchestrators in the defence against S. aureus, but uncertainties persist regarding the subset, polarity, and breadth of the memory CD4 + T cell pool required for protection. Here, using a mouse model of systemic S. aureus infection we discovered that breadth of bacterium-specific memory CD4 + T cell pool is a critical factor for protective immunity against invasive S. aureus infections. Seeding mice with a monoclonal bacterium-specific circulating memory CD4 + T cell population failed to protect against systemic S. aureus infection, however the introduction of a polyclonal and polyfunctional memory CD4 + T cell pool significantly reduced the bacterial burden. Our findings support the development of a multi-epitope T cellbased S. aureus vaccine, as a strategy to mitigate the severity of S. aureus bacteraemia.